The Value of Moderation in Interfaith Life (A Comparative Study of the Perspectives of Buya Hamka and Sayyid Qutb in Qs. Al-Baqarah/2: 256) - Cindy Gayatri; Abdul Muiz (Penerbit Hellow Pustaka, 2026)
Given today's increasingly advanced era, religious communities face various challenges and problems, such as social conflicts based on religion, discrimination against religious minorities, interfaith intolerance, and many other frequently occurring issues. Therefore, religious moderation has become an important theme in the current social and religious context, especially amidst the rise of extremism. This study aims to analyze and compare the perspectives of Sayyid Qutb and Buya Hamka on the value of moderation in interfaith life, as reflected in QS. Al-Baqarah:256, which emphasizes the principle